Feminist Narrativization of trauma in Julia Alvarez’s In the Time of the Butterflies - Pandey, Nabraj (Journal of Tikapur Multiple Campus, 2024)
The study explores on the feminist standpoint of trauma narration in Julia Alvarez's magnum opus, In the Time of the Butterflies. Set against the tragic backdrop of the Mirabel sisters' 1960 massacre and the pervasive exploitation of women during Trujillo's cruel reign in the Dominican Republic, Alvarez intricately weaves personal and political struggles. In this backdrop, the research focuses on Alvarez's use of storytelling techniques to illuminate the traumatic experiences of women, particularly highlighting Dede Mirabel as a testimonial figure in the broader feminist strife. So, the study purposes to unravel the complex layers of feminist discourse within the novel. Utilizing a descriptive based qualitative approach grounded in narrative procedures, this research integrates insights from trauma studies scholars such as Leigh Gilmore, Cathy Caruth, Laura Stark, Hawkins et al., and Jeffrey C. Alexander. The overarching goal is to develop a theoretical framework that elucidates how the novel depicts traumatic experiences within patriarchal structures. This research is significant as it uncovers the intersection of gender and historical trauma, offering a subtle understanding of women steering their experiences amid political oppression. The findings are expected to deepen our grasp of the novel's feminist dimensions and serve as a foundation for future inquiries into the juncture of feminist literature encouraging further exploration of how women's stories shape societal perceptions. Thus, this study lays the groundwork for future research in similar themes across trauma literature.